ADA APA DENGAN INDUSTRI PERTAMBANGAN INDONESIA ? (Sebuah Tinjauan Singkat dari Sudut Pandang Makro Ekonomi) - Yasin, Muhammad; Nurapiah, Nurapiah; Wahab, Abdul; Sakaria, Maulid; Sujarwadi, Sujarwadi (Fakultas Ekonomi Universitas Alkhairaat, 2021)
This study was conducted to determine the benefits and role of the mining industry for the prosperity of Indonesia. In addition, this study also wants to know the contribution of mining to state and regional revenues. And finally, the purpose of this research is to find out the labor absorption capacity of the mining sector industry. This research is a literature research, which includes a study of the thoughts of several figures related to the mining industry. Equipped with empirical data from related agencies, as well as literature searches from various sources of information, interviews were also conducted with a number of parties from both government and private agencies. The information needed is related to the benefits, roles, absorption of labor, and the contribution of the mining industry to the state and region of Central Sulawesi Province. This research was conducted for three months, starting from September 2020 to November 2020 in Palu City, Central Sulawesi Province. The results of the study indicate that the existence of the mining industry in Indonesia can still provide the greatest benefit to the prosperity of the people. The mining industry's contribution to state revenues and mining-producing regions shows a positive trend. The absorption of labor in the mining sector will increase, especially local workers in line with the downstream policy of the mining sector. Keywords: Contribution, Industry, mining, welfare, labor